Investigating the Macroeconomic Determinants of Hosehold Debt in South Africa - Nomatye, Anelisa; Phiri, Andrew (International Journal of Economics and Financial Issues, 2018)
Following the 2007 global financial crisis, the understanding of the relationship between debt and other economic indicators has become crucial for policymakers worldwide. In this study, we investigated the macroeconomic determinants of household debt for the South African economy using macroeconomic variables such as GDP growth, consumption, interest rates, inflation, housing prices and domestic investments. Our mode of empirical investigation is the quantile regression approach which is applied to quarterly time series data spanning from 2002:q1 to 2016:q4. Our empirical results imply that inflation and consumption are insignificantly related with household debt; GDP growth and house prices are only related with household debt at moderate to high levels of distributions whereas interest rates and investment are related with household debt across all quantile distributions. All-in-all, these empirical findings bear important implications for South African policymakers. Keywords: Household debt, Quantile regressions; South Africa. JEL Classifications: C32; C51; R20.